Use of Precision-Cut Tissue Slices as a Translational Model to Study Host-Pathogen Interaction - Majorova, Dominika; Atkins, Elizabeth; Martineau, Henny; Vokral, Ivan; Oosterhuis, Dorenda; Olinga, Peter; Wren, Brendan; Cuccui, Jon; Werling, Dirk (Frontiers in Veterinary Science, 2021)
The recent increase in new technologies to analyse host-pathogen interaction has fostered a race to develop new methodologies to assess these not only on the cellular level, but also on the tissue level. Due to mouse-other mammal differences, there is a desperate need to develop relevant tissue models that can more closely recapitulate the host tissue during disease and repair. Whereas organoids and organs-on-a-chip technologies have their benefits, they still cannot provide the cellular and structural complexity of the host tissue. Here, precision cut tissue slices (PCTS) may provide invaluable models for complex ex-vivo generated tissues to assess host-pathogen interaction as well as potential vaccine responses in a “whole organ” manner. In this mini review, we discuss the current literature regarding PCTS in veterinary species and advocate that PCTS represent remarkable tools to further close the gap between target identification, subsequent translation of results into clinical studies, and thus opening avenues for future precision medicine approaches.